Accelerometer-based vibration analysis and oxygenator thrombosis in venovenous ECMO: an experimental porcine model - Lars Prag Antonsen; Svein Aslak Landsverk; Per Steinar Halvorsen; Amrit Thiara; Didrik Lilja; Naimahmed Nesaragi; Andreas Espinoza (Intensive Care Medicine Experimental)
Abstract Background Oxygenator thrombosis is a potentially life-threatening complication during venovenous extracorporeal membrane oxygenation (VV ECMO). It can cause blood flow obstruction, impaired gas exchange, hematologic abnormalities, or sudden ECMO flow cessation. Early detection and timely circuit exchange is critical yet challenging. Acute clot formation necessitates immediate circuit replacement, while premature replacement risks unnecessary procedural harm and increased costs. No reliable method exists to detect early oxygenator thrombosis. Strategies include visual inspection, monitoring the pressure difference across the oxygenator (ΔP oxy), gas exchange evaluation, and blood tests. In the present animal study, we aimed to evaluate the feasibility of accelerometer-based vibration analysis as a real-time and non-invasive method for detecting oxygenator thrombosis during VV ECMO. We hypothesized that accelerometer signals would change concurrently with or precede increases in ΔP oxy. Methods The study was performed on anesthetized and mechanically ventilated pigs (n = 7) on VV ECMO. Hemodynamic parameters, ECMO circuit pressures, and signals from an accelerometer attached to the ECMO oxygenator were continuously recorded at different pump speeds, and after anticoagulation reversal to promote thrombosis within the ECMO oxygenator. Results The primary finding of this study was a significant increase in the accelerometer signal's Root Mean Squared (RMSoxy) 15 min after anticoagulation reversal, with no rpm adjustment and without corresponding changes in ΔP oxy. Variations in RMSoxy associated with high ECMO pump speed and circuit flow were discernible from those observed following anticoagulation reversal. Conclusion The present animal study demonstrates the feasibility of accelerometer-based vibration analysis as a real-time and non-invasive method for detecting vibrations associated with reversal of anticoagulation and potential oxygenator thrombosis during VV ECMO.